PENGARUH LIFESTYLE DAN WORD OF MOUTH TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN APLIKASI E- MONEY ’’DANA’’ DI KOTA BIMA - Basrin Haryanto; Ismunandar Ismunandar; Ita Purnama (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine lifestyle and word of mouth regarding consumer decisions using the e-money application ''dana''. This research uses observational research. The research results show that lifestyle variables have a partially significant effect on consumers' decisions to use the "Dana" e-money application. The word of mouth variable has a partially significant effect on consumer decisions using the "Dana" e-Money application. Lifestyle variables and word of mouth simultaneously have a significant influence on consumers' decisions to use the "Dana" e-money application.